Phase portraits of the quadratic polynomial Liénard differential systems - Gouveia, Márcio R. A. [UNESP]; Llibre, Jaume; Roberto, Luci Any [UNESP] (Cambridge University Press (CUP), 2020)
We classify the global phase portraits in the Poincaré disc of the quadratic polynomial Liénard differential systems where (x, y) ϵR 2 are the variables and a,b,c,d,e are real parameters.
Keywords: Global phase portraits; Liénard system; Poincaré compactification; Quadratic system